Dermatologic and Dermatopathologic Features of Monogenic Autoinflammatory Diseases - Figueras-Nart, Ignasi; Mascaró, José M.; Solanich, Xavier; Hernández-Rodríguez, José (Frontiers in Immunology, 2019)
Autoinflammatory diseases include disorders with a monogenic cause and also complex conditions associated to polygenic or multifactorial factors. An increased number of both monogenic and polygenic autoinflammatory conditions have been identified during the last years. Although skin manifestations are often predominant in monogenic autoinflammatory diseases, clinical and histopathological information regarding their dermatological involvement is still scarce. Monogenic autoinflammatory diseases with cutaneous expression can be classified based on the predominant lesion: 1) maculopapular rashes or inflammatory plaques; 2) urticarial rashes; 3) pustular, pyogenic or neutrophilic dermatosis-like rashes; 4) panniculitis or subcutaneous nodules; 5) vasculitis or vasculopathy; 6) hyperkeratotic lesions; 7) hyperpigmented lesions; 8) bullous lesions; and 9) aphthous lesions. By using this classification, this review intends to provide clinical and histopathological knowledge about cutaneous involvement in monogenic autoinflammatory diseases.